Laporan Kasus: Kista Ovarium Permagna - Muhammad Yusuf; Achmadi (Direktorat Penerbitan dan Publikasi Ilmiah, Universitas Surabaya, 2022)
Abstract—Giant ovarian cyst is a mass on the adnexa with a size of 10 cm before surgery. About 10% of women will have tumor growths on the ovaries and almost all of them are benign. In this case a 50-year-old woman with complaints of an enlarged abdomen, abdominal fullness and malaise. The result of the ultrasonography picture obtained lobed masses with a diameter of 20 cm. After that, a total abdominal hysterectomy operation with bilateral salphyngoophorectomy is performed. The operation went well and the patient went home without any follow-up problems. Lab results found CA 125 levels of 20.87 U/mL, with histological descriptions stating these cysts are benign and contain mucin fluid. Keywords: ovarian, cyst, giant, mucinous, benign Abstrak—Kista ovarium permagna merupakan massa pada adneksa dengan ukuran 10 cm sebelum operasi. Sekitar 10% wanita akan mengalami pertumbuhan tumor pada ovarium dan hampir semuanya jinak. Pada kasus ini wanita berusia 50 tahun dengan keluhan perut semakin membesar, rasa penuh dan tidak enak. Hasil gambaran ultrasonography didapatkan massa berlobus – lobus dengan diameter 20 cm. Setelah itu, dilakukan operasi total abdominal hysterectomy dengan bilateral salphyngoophorectomy. Operasi berjalan dengan baik dan pasien pulang tanpa ada masalah lanjutan. Hasil lab ditemukan kadar CA 125 20.87 U/mL, dengan gambaran histologi menyatakan kista ini jinak dan berisi cairan mucin. Kata kunci: kista, ovarium, mucin, permagna